Determinants and issues of Libyan-Turkish Relations (Journal of Human Sciences, 2021)
This research aims to know the most important determinants that control the Libyan-Turkish relations. It also identifies the most important issues that obstruct the relationship development since 2011. The research problem has been formulated in the following research questions: What are the most important determinants that govern the Libyan-Turkish relations? What are the issues that obstruct the relationship development? In line with the questions raised, the answer to them stemmed from a basic assumption that the Libyan-Turkish relations are governed by several political and economic determinants. This resultes in a set of issues that interfered with the course of their development. These issues led to the fluctuation of those relations between cases of rapprochement and cooperation at certain historical stages, and between divergence and tension in other historical stages. The research concluded that the opportunities for rapprochement in the economic fields between the two countries are great, especially with the stability of the Libyan state, its orientation towards development, and the reconstruction of what was destroyed by internal wars. What enhances these opportunities is the previous activity of Turkish construction companies that have been operating in Libya for more than forty years. This is in addition to the Turkish investment opportunities in the Libyan energy sector. However, this rapprochement requires a political environment that contributes to strengthening confidence and removing all controversial issues related to the Turkish intervention in Libya.